2020
DOI: 10.1002/jpen.2013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Enteral Erythromycin Estolate in Combination With Intravenous Metoclopramide vs Intravenous Metoclopramide Monotherapy in Mechanically Ventilated Patients With Enteral Feeding Intolerance: A Randomized, Double‐Blind, Controlled Pilot Study

Abstract: Background In this pilot study, we aimed to determine the efficacy and safety of enteral erythromycin estolate in combination with intravenous metoclopramide compared to intravenous metoclopramide monotherapy in mechanically ventilated patients with enteral feeding intolerance. Methods This randomized, double‐blind, controlled pilot study included 35 mechanically ventilated patients with feeding intolerance who were randomly assigned to receive 10‐mg metoclopramide intravenously every 6–8 hours in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
3
9
0
Order By: Relevance
“…In our study, nutrition risk and illness severity were high similar to results of a recent randomized controlled trial [25] while they were evidently higher than those in previous study [41].…”
Section: Secondary Outcomessupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, nutrition risk and illness severity were high similar to results of a recent randomized controlled trial [25] while they were evidently higher than those in previous study [41].…”
Section: Secondary Outcomessupporting
confidence: 87%
“…Likewise, to the results of our study, a recent RCT reported that intravenous metoclopramide caused significantly higher accumulative GRV than another prokinetic (erythromycin estolate) combined with metoclopramide when used for EFI in critically ill patients [25].…”
Section: Primary Outcomesupporting
confidence: 87%
See 1 more Smart Citation
“…Patients with EFI received either domperidone (10 mg administered via tube feeding every 8 h) or metoclopramide (10 mg administered as a 50-mL IV infusion over 30 min every 8 h) [ 11 ]. The dose of IV metoclopramide was 50% of normal dose in patients with creatinine clearance ≤40 mL/min and 25% in patients with clearance ≤10 mL/min or undergoing dialysis or continuous renal replacement techniques [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most studied prokinetic agent in both ICU and non-ICU settings was metoclopramide (49%) followed by erythromycin (31%). 18,20,21,24,25,28,33,34,36,[40][41][42]45,46,49,52,56,59,60,67,69,70,[72][73][74]84,93,96,[100][101][102]105,106,109,113,114 Other agents included serotonin receptor agonists (cisapride, mosapride, prucalopride, TAK-954) (18%) and dopamine antagonists (domperidone and itopride) (10%). Five studies investigated alternative interventions as prokinetic agents, for example, three studies investigated acupuncture.…”
Section: Type Of Prokinetic Agentsmentioning
confidence: 99%